The role of gender in patients with diffuse large B cell lymphoma treated with rituximab-containing regimens: a meta-analysis - Yıldırım, Mustafa (Arch Med Sci, 2015)
INTRODUCTION: Diffuse large B cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma (NHL). Although gender has not been included in prognostic systems, male gender has been found as a bad prognostic indicator in Hodgkin lymphoma, follicular lymphoma and chronic lymphocytic leukemia. The relationship between gender and prognosis is not clear in patients with DLBCL treated with rituximab-containing regimens. The aim of this meta-analysis is to determine the prognostic/predictive role of gender in patients with DLBCL treated with rituximab-containing regimens. MATERIAL AND METHODS: We systematically searched for studies investigating the relationships between gender and prognosis in DLBCL treated with rituximab-containing regimens. After careful review, survival data were extracted from eligible studies. A meta-analysis was performed to generate combined hazard ratios for overall survival, disease-free survival (DFS) and event-free survival (EFS). RESULTS: A total of 5635 patients from 20 studies were included in the analysis. Our results showed that male gender was associated with poor prognosis in terms of overall survival (OS) (hazard ratio (HR) = 1.155; 95% confidence interval (CI): 1.037–1.286; p < 0.009). The pooled hazard ratio for DFS and EFS showed that male gender was not statistically significant (HR = 1.219; 95% CI: 0.782–1.899; p = 0.382, HR = 0.809; 95% CI: 0.577–1.133; p = 0.217). CONCLUSIONS: The present meta-analysis indicated male gender to be associated with a poor prognosis in patients with DLBCL treated with rituximab-containing regimens.